Exclusive Breastfeeding and Exposure to Cigarette Smoke with The Incidence of Acute Respiratory Infection in Children Under Five - Asmita Hi. Ashar (Media Publikasi Cendekia Indonesia, 2022)
Acute Respiratory Infection (ARI) is an infection of the respiratory tract, either the upper or lower respiratory tract. This disease is caused by bacteria or viruses that enter the respiratory tract and cause an inflammatory reaction. ARI is one of the most common diseases in children under five who visit the Singgani Health Center. This study aims to determine what factors are associated with ARI incidence in children under five at the Singgani Health Center, Palu City. This study uses an observational analytic method with a Cross-Sectional Study design. The number of samples used was 77 samples using the purposive sampling technique. The data was collected using a questionnaire; the data was then analysed using the Chi-square test with univariate and bivariate analysis on SPSS. The results of this study indicate that there is a relationship between exclusive breastfeeding (p = 0.00) and exposure to cigarette smoke (p = 0.02) with the incidence of ARI in children under five. There is no relationship between nutritional status (p = 0.33) and giving colostrum (p=0.66) with the incidence of ARI in children under five at the Singgani Health Center, Palu City. Suggestions for Puskesmas are to provide information and counselling related to the importance of exclusive breastfeeding and the dangers of cigarette smoke and reduce the prevalence of ARI in children under five